2016
DOI: 10.1021/acs.joc.6b02023
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry of 1- and 2-Methyl-5-aminotetrazoles: Structural Effects on Reaction Pathways

Abstract: The influence of the position of the methyl substituent in 1- and 2-methyl-substituted 5-aminotetrazoles on the photochemistry of these molecules is evaluated. The two compounds were isolated in an argon matrix (15 K) and the matrix was subjected to in situ narrowband UV excitation at different wavelengths, which induce selectively photochemical transformations of different species (reactants and initially formed photoproducts). The progress of the reactions was followed by infrared spectroscopy, supported by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 36 publications
2
16
0
Order By: Relevance
“…Nevertheless, under the experimental conditions used, the antiaromatic three membered ring 7 could indeed be generated as the sole photoproduct and was found to be photostable. This result is even more remarkable because, contrarily to what is observed in this case, the diazirene derivative of 2-methyl-5-aminotetrazole was found to react upon irradiation at 325 nm [33]. On the other hand, the observed photostability of the antiaromatic three membered diazirene 7 follows the trend observed for a previously studied S-linked tetrazole-saccharinate [10], and appears to be a common phenomenon on this type of conjugates, probably induced by the stabilizing effect of the electron-withdrawing saccharyl moiety.…”
Section: Photochemistry Of Matrix-isolated 2-methyl-5-aminotetrazole-supporting
confidence: 63%
See 3 more Smart Citations
“…Nevertheless, under the experimental conditions used, the antiaromatic three membered ring 7 could indeed be generated as the sole photoproduct and was found to be photostable. This result is even more remarkable because, contrarily to what is observed in this case, the diazirene derivative of 2-methyl-5-aminotetrazole was found to react upon irradiation at 325 nm [33]. On the other hand, the observed photostability of the antiaromatic three membered diazirene 7 follows the trend observed for a previously studied S-linked tetrazole-saccharinate [10], and appears to be a common phenomenon on this type of conjugates, probably induced by the stabilizing effect of the electron-withdrawing saccharyl moiety.…”
Section: Photochemistry Of Matrix-isolated 2-methyl-5-aminotetrazole-supporting
confidence: 63%
“…From the very first studies [32], it was postulated that the parent tetrazole in its gas phase most stable isomeric 2H-form, as well as 2-, 5-and 2,5-substituted tetrazoles, undergo fragmentation through formation of a nitrile imine intermediate that cyclizes to a 1H-diazirene, then leading to a final carbodiimide through rearrangement. However, this pattern of reactivity was demonstrated experimentally only very recently, during studies on the photochemistry of tetrazoles under low-temperature matrix isolation conditions [5,13,15,21,33,35]. The observed outline of photo-fragmentation of 4 upon irradiation at λ = 250 nm follows this general pattern, which, as also found in other cases [10,33], is accompanied by an additional reaction path involving as reactant the 1H-diazirene (see Scheme 3).…”
Section: Photochemistry Of Matrix-isolated 2-methyl-5-aminotetrazole-mentioning
confidence: 76%
See 2 more Smart Citations
“…An additional interest of this substitution pattern resides in the potential of 2,5-disubstituted tetrazoles to act as probes. It was demonstrated that, upon narrow-band UV-induced irradiation, 2,5-dissubstituted tetrazoles generate nitrile imine dipolar species in situ, via extrusion of N 2 , which may then react with an alkene dipolarophile through a 1,3-dipolar cycloaddition reaction [ 49 , 50 ]. Thus, the trioxolane–tetrazole conjugates LC131 and LC136 could also be developed as tags for mechanistic studies.…”
Section: Discussionmentioning
confidence: 99%